Problematika reprezentacije spola v ruščini. Ali je v ruščini v bližnji prihodnosti možno doseči spolno nevtralnost? - Leonidovna Grigoryeva, Leona (Slavia Centralis, 2023)
This article is aimed at the study of different aspects of gender linguistics in the Russian language, namely the history of the evolution of gender linguistics in Russia, the grammatical category of gender, gender vocabulary and phraseology, differences between men’s and women’s use of the language, and the issue of gender neutrality in Russian. The study is based on the latest research work in this field of linguistics, which has developed rapidly in the Russian Federation and the former Soviet countries in recent decades. By gender linguistics we refer to a branch of linguistics that studies various aspects of gender representation in language. The study of gender aspects of the Russian language throws light on the linguistic picture of the world of the native speakers and helps us understand their worldview, cultural values and outlook on social roles in terms of gender. The author outlines the future perspectives of study in the field of gender representation in Russian and evaluates the possibilities of Russian becoming a gender neutral language.